Kadar Sianida Dan Tiosianat Pada Tikus Putih Postmortem Yang Diberi Sianida Dosis Letal Secara Per Oral - I.B.Gd. Surya P dan Suhartini (Berita Kedokteran Masyarakat (BKM), 2004)
Background: The examinations of forensic corpse have to be performing an autopsy and laboratory examination to determine cause of death of the victim. However in the case of death suspected as cyanide person was often difficult to determine cause of death of the victim, because the result of laboratory examination did not f Conorrn to our expectations. As that have to be done the study about poison of cyanide, is usedf oi cyanide and tyosianat can be still detected by spectrophotometer in different sample and SParfl Of fine"). Objective: to find out the connection between level of cyanide and tyosianat as metabolite in the lever and kidneys of white mouse given per oral lethal dose cyanide with the time of blood, examination.The Result of study was used as reference to examine an exact sampel in the case of cyanide poison. Methods: Study design used experimental quasi, that are three white mouse of wistar with 100200 g of weight given KCN 3 mg/kg of weight. After mouse died, the blood of mouse was taken by venous then performs an autopsy to obtain lever and kidneys. Each of the sampels was divided into three groups. One group was examined in flat time, two weeks and four weeks. Cyanide was examined by methods of pyridine acid barbiturate and tyosianat was examined by method of tri chloro acetate, then the examination of spectrophotometers have to be done the data was counted by correlation of standard curve. Results: The examination of tyosionat level was obtained more higher in the four weeks than at the time and two weeks. However, the level of cyanide was obtained higher at that time than in two weeker s and than four neys and b lo kid weeks. The lod.evel of cyanide and tyosianat in the organs was obtained higher in the live Conclusion: The examination of cyanide poison had better to be done at the time and tyosianat was examined in four weeks, the liver had better to be examined than kidneys and blood. Keywords: an autopsy, cyanide poison, level of cyanide and tyosianat, spectrophotometer examination